2018
DOI: 10.15171/icnj.2018.18
|View full text |Cite
|
Sign up to set email alerts
|

The Structural Model of Educational Self-regulation Based on Learning Strategies and Attributional Styles by the Mediator of Achievement Motivation Among Secondary High School Students in Sari in 2017-2018

Abstract: Background: Achievement motivation is one of the critical variables that predict educational achievement and success in the future. Therefore, the identification of effective factors upon achievement motivation may be one of the basic subjects in education. The present study aimed to evaluate the structural model of educational self-regulation based on learning strategies by the mediator of achievement motivation among students. Methods: The present study was correlation research with structural equation model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…The present study investigated the association between attributing academic success to giftedness and students' academic achievement, with students' negative learning emotions and self-regulated learning being included as mediators. In line with our hypotheses (Dent & Koenka, 2016;Pekrun et al, 2017;Shirdel et al, 2018), students with higher levels of AAS_G had higher levels of SRL and lower levels of NLE, and an increased SRL and a decreased NLE led to a better academic achievement. Our findings provided support for the Attribution Theory (Weiner, 2006) that causal attribution would affect students' emotions and behaviors and thereafter affect their academic achievement.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The present study investigated the association between attributing academic success to giftedness and students' academic achievement, with students' negative learning emotions and self-regulated learning being included as mediators. In line with our hypotheses (Dent & Koenka, 2016;Pekrun et al, 2017;Shirdel et al, 2018), students with higher levels of AAS_G had higher levels of SRL and lower levels of NLE, and an increased SRL and a decreased NLE led to a better academic achievement. Our findings provided support for the Attribution Theory (Weiner, 2006) that causal attribution would affect students' emotions and behaviors and thereafter affect their academic achievement.…”
Section: Discussionsupporting
confidence: 89%
“…Students who engaged in self-regulated learning would be motivated to exert control over a wide range of behaviors such as concentrating in classes (Sitzmann & Ely, 2011), and this process may be affected by their attribution of academic success. For example, Shirdel et al (2018) found that attributing positive events to internal factors would enhance students' motivation for learning, and further promote their SRL. Specifically, when students attributed successes to internal factors, they would predict the result to repeatedly occur in the near future, and therefore show higher levels of engagement and motivation in the learning process (Sun & Xie, 1993).…”
Section: Achievement Attribution Negative Learning Emotions and Selmentioning
confidence: 99%
See 2 more Smart Citations
“…These varied self-theories influence the way they perceive knowledge and abilities, self-regulating learning, interpreting and managing challenges within the academic situation (Lawson, Vosniadou, Van-Deur, Wyra and Jeffries, 2019;Yeager and Dweck, 2020). For example, Shirdel, Fakhri and Mirzaeyan (2018) found that attributing positive events to internal factors would enhance students' motivation for learning and further promote their self-regulated learning. Such students exercise greater control of their lives, including navigating their learning and selfregulating.…”
Section: Theoretical Frameworkmentioning
confidence: 99%